Workshop Emo-Demo bagi Tenaga Puskesmas Kota Padang - Kamal Kasra; Adila Kasni Astiena; Ade Betasril; Dicki Kurnia Pratama (Warta Pengabdian Andalas)
One of the nutritional problems in children indicated by stunting is a risk factor for impaired immune function. The most significant component of the immune system is nutrients that generally cannot be produced by the body but depend on various food intakes. The Faculty of Public Health, Andalas University, assisted several urban villages in Padang City. Efforts to improve the skills of the existing Public Health Services in each area need to be optimized. One form of activity that was carried out was a workshop on Emo-Demo. This activity's output target was to increase health workers' knowledge and skill to educate cadres of public health service in increasing children's immunity during the pandemic and prevent stunting with the Demo method. This activity went smoothly, and all Public Health Centre officers were enthusiastic about participating. Public Health Centre officers can train the cadres in their working area with Emo-Demo skills.